Personal Values and Innovative Behavior of Employees - Purc, Ewelina; Laguna, Mariola (Frontiers in Psychology, 2019)
Innovations are based on the good ideas of individuals; therefore, it is very important to better understand the role that individuals and their personal characteristics play in innovative initiatives. The aim of the current study was to test the relationships between employees’ personal values and their innovative behaviour. It was hypothesised that these relationships are mediated by an employee’s job autonomy. We integrated Schwartz’s basic human values theory with the notion that job autonomy is an important job characteristic that can be redesigned to better fit employee preferences. The study results (obtained from 263 employees in different branches) showed that openness to change and self-enhancement values are positively related to job autonomy, whereas conservation and self-transcendence values are negatively related to job autonomy, which confirms that personal values are important in explaining autonomy in the workplace. In addition, employees’ self-enhancement values are positively related to their innovative behaviour, while conservation and self-transcendence values are negatively related to innovative behaviour. Mediation analysis with a bias-corrected bootstrapping method showed that job autonomy is a significant mediator of the relationships between employees’ personal values (except for openness to change) and their innovative behaviour. Our research extends the theory of basic human values, showing that values serve as a personal basis for innovative behaviour. Our results also contribute to the innovation research by demonstrating the importance of personal values and job autonomy for innovative behaviour in organisations.